2018
DOI: 10.1186/s40479-018-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

A whole of school intervention for personality disorder and self-harm in youth: a pilot study of changes in teachers’ attitudes, knowledge and skills

Abstract: BackgroundThe school environment offers an ideal opportunity for early identification and intervention for youth with self-harm and complex mental health issues, such as borderline personality disorder (BPD). Yet, class teachers often report minimal knowledge, feeling ill-equipped to respond, and experience high levels of stress when exposed to such challenges. Research is required to understand how training and development activities led by school counsellors may enhance teacher attitudes, confidence and know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Post-training evaluation found that there was significant improvement in confidence, skill and knowledge of school staff towards self-harm, and that these improvements were sustained at a six-month follow-up. In 2018, the current authors collaboratively developed accredited training for teachers, and found that providing teachers with additional training on complex mental health issues and associated behaviours, such as self-harm, was well received (Townsend et al, 2018). Our results indicated improvements in class teachers' knowledge and attitudes towards self-harm and complex mental health issues.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Post-training evaluation found that there was significant improvement in confidence, skill and knowledge of school staff towards self-harm, and that these improvements were sustained at a six-month follow-up. In 2018, the current authors collaboratively developed accredited training for teachers, and found that providing teachers with additional training on complex mental health issues and associated behaviours, such as self-harm, was well received (Townsend et al, 2018). Our results indicated improvements in class teachers' knowledge and attitudes towards self-harm and complex mental health issues.…”
mentioning
confidence: 67%
“…Essentially though, self harm is any behaviour where a person intentionally sets out to harm themselves. – Wellsway School (2018, p. 2)One policy (Government of Western Australia, 2017) used the term ‘non-suicidal self-injury’. This policy emphasised that the aim of self-harm behaviours was to reduce or cope with distressing emotions, with no intent that this behaviour would result in death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, where there is imminent risk, escalation to emergency services is necessary (Townsend, Hasleton, Marceau, Gray, & Grenyer, 2018b). Providing schools with structured responses can assist the capacity of schools to plan and implement strategies to support students (Townsend et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…School staff have a unique role in the detection and response to mental health issues, including self-harm and suicidal behaviours (Hasking et al, 2016;Townsend, Gray, Lancaster, & Grenyer, 2018a). In a survey of 15-19 year olds, 36% reported they would go to a teacher if they needed help while 30.4% reported they would turn to a school counsellor (Carlisle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%